Relationship Between Emotional Intelligence and Geography Learning Outcomes of Class XII Students at Wahdah Islamiyah Integrated Islamic High School Makassar - Abbas, Ibrahim; Syarif, Erman; Lisman, Lisman (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to determine whether there is a relationship between emotional intelligence and geography learning outcomes in class XII Islamic Senior High School Wahdah Islamiyah Makassar. This research is a type of quantitative research with the Spearman Rank correlation method. The data collection technique uses a questionnaire. The sampling technique in this study used a saturated sampling technique with a total of 25 respondents. For learning outcomes data is taken from the grade XII student report cards in the geography subject. The results of the analysis of emotional intelligence data are included in the medium category with an average value = 107.84 at intervals 103–110, for geography learning outcomes are included in the low category with an average value = 83.52 at intervals 81-84, to prove whether or not there is a relationship between emotional intelligence and geography learning outcomes, it can be seen from the calculation obtained using the Spearman Rank correlation formula, where the value of rs =0.037, with a significant value of 0.861. Because sig > 0.05, it can be concluded that emotional intelligence does not have a significant relationship with geography learning outcomes and the relationship is included in the very low category.